Bibliometric analysis of African Journal Of Library, Archives and Information Science from 2000-2012. Issue 4 (1st July 2014) - Tella, Adeyinka; Aisha Olabooye, Ayotola
Abstract : Purpose: – This study aims to examine the pattern of publications, using a bibliometric analysis, of the African Journal of Library, Archives and Information Science (AJLAIS) for the period between 2000 and 2012. Design/methodology/approach: – The study uses appropriate measures and techniques of bibliometric analysis. Keeping the objectives of the study in mind, the data were collected from the AJLAIS covering the 13 identified years. The analysis covers mainly the number of articles published per volume in each of the specified years, the authorship patterns, the subject areas covered, the length of articles, the citation pattern of articles and the article types. Findings: – The results of the study reveal that a total of 218 articles were published in the 13-year period, with 21 (9.63 per cent) articles being the highest total in the year 2002. The study showed that the majority of the articles, i.e. 126 (57.8 per cent), were published by single authors, out of which, a large number were on information retrieval. Of the total number of articles published, 86 (39.4 per cent) were 6-10 pages in length. Volume 19 in 2009 had the highest number of citations with a total of 451 (12.4 per cent). In addition, the study revealed that the majority of the articles were theoretical papers, with a total of 108 (49.5 per cent), while the others were empirical papers, book reviews and short communications. Practical implications: – This bibliometric study will enlarge the knowledge base of information professionals on the present condition of library and information science (LIS) research in the current African context and provide some basis for future projections of the discipline. The study will also be helpful for librarians in the process of collection development. This is because, due to increased journal costs and slim budgets for libraries, collection development specialists must make careful selections based on the qualities and standards of journals. Originality/value: – Researchers who shy away from this particular type of research owing to its rigorous and time-consuming nature should gather the courage to do so. Further studies should focus on analysing journals that are published in the field of librarianship in Africa, as it will create more awareness of the field of study among other professionals or researchers who are yet to know about it. The study has also revealed AJLAIS as one of the LIS standard journals in terms of its wider citation by contributors in the broader LIS literature.